Argentina : Can Short Term Incentives Change Long Term Behavior? - World Bank (Washington, DC, 2015)
After an economic crisis in Argentina in 2001 plunged millions of people there into poverty and worsened health outcomes, especially for women and children, the government crafted a new, national plan for a provincial health insurance program for the poor. The program, called Plan Nacer, was specifically designed for pregnant women without health coverage and children up to the age of six (the program has since been expanded to include other groups). Under the program, which was launched in 2005, the national government transfers money to the provinces to use for health services, basing part of the payment on how well the province has done at meeting certain health indicators. An evaluation of the program found that setting up the financial incentives this way led to an improvement in health care, as measured by a drop in low birth weight babies and a decline in newborn deaths. As the results of this impact evaluation show, temporary incentives are an effective way to motivate health care workers to change their routines so that ultimately, they’re providing better care for the people they’re tasked to serve. The results will be particularly useful to policy makers looking to make long-term changes more cheaply than traditional pay-for-performance programs. Nevertheless, the results also highlight the challenge of improving birth outcomes for high-risk populations. As researchers continue to search for innovative ways to help the world’s poor, the lessons from this intervention underscore the importance of providing solutions that specifically target those who need it most.